The Effect Of Perceived Risk, Consumer Lifestyle And Online Trust On The Purchase Intention Of Fashion Products In Instagram Social Media - Taranggana Ari Sakti; Sukaris Sukaris; Asep Saepuloh (INNOVATION RESEARCH JOURNAL, 2020)
This study aims to analyze the effect of perceived risk, consumer lifestyle and online trust on the purchase intention of fashion products on Instagram social media in Surabaya. The sample in this study consisted of 75 respondents. The independent variable in this study is perceived risk, consumer lifestyle and online trust, while the dependent variable is the purchase intention of fashion products on Instagram. The data analysis technique used is multiple linear regression with the help of the SPSS program. The results showed that the variable perceived risk, consumer lifestyle and online trust partially influenced the interest in buying fashion products on Instagram social media in Surabaya